2011
DOI: 10.1186/1757-1146-4-25
|View full text |Cite
|
Sign up to set email alerts
|

Forefoot pathology in rheumatoid arthritis identified with ultrasound may not localise to areas of highest pressure: cohort observations at baseline and twelve months

Abstract: BackgroundPlantar pressures are commonly used as clinical measures, especially to determine optimum foot orthotic design. In rheumatoid arthritis (RA) high plantar foot pressures have been linked to metatarsophalangeal (MTP) joint radiological erosion scores. However, the sensitivity of foot pressure measurement to soft tissue pathology within the foot is unknown. The aim of this study was to observe plantar foot pressures and forefoot soft tissue pathology in patients who have RA.MethodsA total of 114 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
3
15
0
3
Order By: Relevance
“…Bowen et al [29] also found that erosions of the MTP joint predominantly appear in the lateral half of the forefoot of the patients with RA.…”
Section: Metatarsophalangeal (Mtp) Joints Synovial Hypertrophy and Efmentioning
confidence: 93%
“…Bowen et al [29] also found that erosions of the MTP joint predominantly appear in the lateral half of the forefoot of the patients with RA.…”
Section: Metatarsophalangeal (Mtp) Joints Synovial Hypertrophy and Efmentioning
confidence: 93%
“…This might be the result of advances in early referral and tight disease control in RA in recent years. Moreover, a forefoot offloading strategy was detected in some patients [26,27]. In these patients, using FOs could normalize forefoot loading, resulting in increased forefoot PTI after FO intervention while in other patients decreased forefoot PTI after FO intervention was achieved.…”
Section: Discussionmentioning
confidence: 97%
“…Pedobarography method is used to assess physical leg overload. It is non-invasive and enables us to monitor changes in musculoskeletal system biomechanics [10].…”
Section: Disscusionmentioning
confidence: 99%